Participation in bowel screening among men attending abdominal aortic aneurysm screening. Issue 5 (21st February 2018) - Quyn, A J; Fraser, C G; Rodger, J; Digan, A; Anderson, A S; Steele, R J C
Abstract: Background: Uptake of population-based screening for colorectal cancer in Scotland is around 55 per cent. Abdominal aortic aneurysm (AAA) screening has recently been introduced for men aged 65 years and the reported uptake is 78 per cent. The aim was to determine the impact of a brief intervention on bowel screening in men who attended AAA screening, but previously failed to complete bowel screening. Methods: Men invited for AAA screening between September 2015 and March 2016 within NHS Tayside were included. Attendees who had not responded to their latest bowel screening invitation were seen by a colorectal cancer clinical nurse specialist. Reasons for not completing the faecal occult blood test (FOBT) were recorded; brief information on colorectal cancer screening was communicated, and participants were offered a further invitation to complete a FOBT. Those who responded positively were sent a further FOBT from the Scottish Bowel Screening Centre. Subsequent return of a completed FOBT within 6 months was recorded. Results: A total of 556 men were invited for AAA screening, of whom 38·1 per cent had not completed a recent FOBT. The primary reason stated for not participating was the time taken to complete the test or forgetting it (35·1 per cent). Other reasons included: lack of motivation (23·4 per cent), confusion regarding the aim of screening (16·2 per cent), disgust (19·8 per cent), fear (6·3 per cent) and other health problems (9·9 per cent). Following discussion, 81·1 per cent agreed to complete the FOBT and 49 per cent subsequently returned the test. Conclusion: A substantial proportion of previous bowel screening non-responders subsequently returned a completed FOBT following a brief intervention with a nurse specialist. Attendance at non-bowel screening appointments may provide a valuable opportunity to improve bowel screening uptake. Abstract : Maximizing screening benefits